Coextrusion of polymeric piezoelectric filaments - Martins, R. S. (2012)
The difficulties related to the development of industrial scalable production methodologies have limited the number of applications currently available in the field of interactive/electronic textiles, which are far below the anticipated a few years ago. In these areas the integration of piezoelectric materials, that possess sensing/actuating capabilities, such as poly(vinylidene fluoride), PVDF, and can be processed using conventional processing techniques, is very promising and has encouraged a large number of research works. However, until now, most of the developed production methodologies are difficult to adapt to the industrial scale. This work reports recent developments achieved in the framework of a research project, on the production of piezoelectric filament by coextrusion of PVDF and an electrically conductive thermoplastic. The developed production methodology is based on a conventional coextrusion line, for which a coextrusion die was designed to produce a multilayer filament, which comprises an inner layer of an electrically conductive Polypropylene grade and a middle layer of PVDF and is coated with an electrical conductive ink. The sensing capabilities of the produced filaments are also characterized.